Association of diet quality and food insecurity with metabolic syndrome in obese adults - Ahmed Abdurahman (Wolters Kluwer Medknow Publications, 2021)
Background: The link between diet quality, food insecurity (FI), and metabolic syndrome (MetS) remains unclear in obese adults. The aim of this study was to examine the association of diet quality and FI with MetS in obese Iranian adults. Methods: This cross-sectional study was conducted on 300 obese adults. Dietary intake was assessed using a validated 168-item food frequency questionnaire. Diet quality and FI were measured using the Diet Quality Index-International (DQI-I) and an adapted USDA2000 household food security status questionnaire, respectively. MetS was defined according to the International Diabetes Federation diagnostic criteria. Association was determined using logistic regression analysis adjusting for potential confounders. Results: MetS subjects had lower DQI-I score than subjects without MetS (67.5 ± 8.7 vs 71.5 ± 7.4, P = 0.05). The prevalence of food insecurity was 48.6% (95% confidence interval (CI): 41.2, 56.1) in MetS subjects and 39.4% (95% CI: 29.4, 49.9) in subjects without MetS. After adjustment, participants in the fourth quartile of DQI-I score had 70% lower odds of MetS (Adjusted odds ratio [AOR], 0.3; 95% CI: 0.1–0.7), 70% lower odds of hypertriglyceridemia (AOR, 0.3; 95% CI: 0.2–0.7) and 60% lower risk of reduced high-density lipoprotein [HDL] (AOR, 0.4; 95% CI: 0.2–0.9) compared with the first quartile. Obese food insecure adults had 60% higher odds of high blood pressure (AOR, 1.6; 95% CI: 1.0–2.6) and 70% higher odds of hypertriglyceridemia (AOR, 1.7; 95% CI: 1.0–2.8) compared with food-secure obese adults. There was no statistically significant interaction observed between DQI-I and food insecurity on MetS. Conclusions: Lower DQI-I score and food insecurity were associated with an increased risk of MetS and some features such as hypertriglyceridemia, reduced HDL, and high blood pressure in obese Iranian adults.